PENGARUH MEDIA POHON PINTAR TERHADAP KEMAMPUAN MENGENAL HURUF PADA ANAK USIA 4-5 TAHUN - Siti Nurbadrin; Setiyo Utoyo; Sri Wahyuningsi Laiya (Student Journal of Early Childhood Education, 2021)
This purpose of this research was to determine the effect of Smart Tree media on the ability to recognize letters in children aged 4-5 years in Raudhatul Athfal Almourky, Telaga District, Gorontalo Regency. The sampling technique in this study was using a purposive sampling technique with a total of 25 children. The research method used is quantitative research with a one group pre-posttest design. The results of the study illustrate that there is a difference between the ability to recognize letters before using smart tree media and after, it can be proven by the number of average values before using smart tree media is 25.2 while the average value after using smart tree media is 42.36. Through the smart tree, children can recognize letters through play-based learning in accordance with the stages of early childhood learning so as to foster self-confidence in children, and improve language development aspects.